Dihydrotanshinone Inhibits Hepatocellular Carcinoma by Suppressing the JAK2/STAT3 Pathway - Hu, Xue; Jiao, Fangzhou; Zhang, Lan; Jiang, Yingan (Frontiers in Pharmacology, 2021)
Liver cancer is the sixth most commonly diagnosed cancer and the fourth leading cause of cancer death. Most (75–85%) primary liver cancers occurring worldwide are hepatocellular carcinoma (HCC). The development of resistance and other drug related side effects are the prime reasons for the failure of treatment. Therefore, developing high-efficacy and low-toxicity natural anticancer agents is greatly needed in the treatment of HCC. Dihydrotanshinone (DHTS) is widely used for promoting blood circulation and antitumor. The aim of the present study was to investigate the effect and mechanism of DHTS-induced apoptosis of HCC, both in vitro and in vivo. We found that DHTS inhibited the growth of several HCC cells (HCCLM3, SMMC7721, Hep3B and HepG2). DHTS induced the apoptosis of SMMC7721 cells. Immunofluorescence results have showed that DHTS decreased STAT3 nuclear translocation. Moreover, Western blot results have demonstrated that DHTS suppressed the activation of JAK2/STAT3 signaling pathway. In addition, xenograft results have showed that DHTS suppressed tumor growth of SMMC7721 cells in vivo by inhibiting the p-STAT3. Thus, we demonstrated that DHTS could inhibit HCC by suppressing the JAK2/STAT3 pathway. DHTS has potential to be a chemotherapeutic agent in HCC and merits further clinical investigation.